Crisis in LAC : Infrastructure Investment and the Potential for Employment Generation - Tuck, Laura; Schwartz, Jordan; Andres, Luis (World Bank, Washington, DC, 2012)
Infrastructure investment is a central part of the stimulus plans of the Latin America and Caribbean Region (LAC) as it confronts the growing financial crisis. This paper estimates the potential effects on direct, indirect, and induced employment for different types of infrastructure projects with LAC-specific variables. The analysis finds that the direct and indirect short-term employment generation potential of infrastructure capital investment projects may be considerable-averaging around 40,000 annual jobs per US$1billion in LAC, depending upon such variables as the mix of subsectors in the investment program; the technologies deployed; local wages for skilled and unskilled labor; and the degrees of leakages to imported inputs. While these numbers do not account for substitution effect, they are built around an assumed "basket" of investments that crosses infrastructure sectors most of which are not employment-maximizing. Albeit limited in scope, rural road maintenance projects may employ 200,000 to 500,000 annualized direct jobs for every US$1billion spent. The paper also describes the potential risks to effective infrastructure investment in an environment of crisis including sorting and planning contradictions, delayed implementation and impact, affordability, and corruption.